2015
DOI: 10.1128/iai.00970-15
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuni Increases Flagellar Expression and Adhesion of Noninvasive Escherichia coli: Effects on Enterocytic Toll-Like Receptor 4 and CXCL-8 Expression

Abstract: cCampylobacter jejuni is the most common cause of bacterium-induced gastroenteritis, and while typically self-limiting, C. jejuni infections are associated with postinfectious intestinal disorders, including flares in patients with inflammatory bowel disease and postinfectious irritable bowel syndrome (PI-IBS), via mechanisms that remain obscure. Based on the hypothesis that acute campylobacteriosis may cause pathogenic microbiota dysbiosis, we investigated whether C. jejuni may activate dormant virulence gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 89 publications
0
21
0
Order By: Relevance
“…[6] and Camplylobacter spp. [7]. However, early data suggest that even the much more common bacterial cause of traveler’s diarrhea, Enterotoxigenic Escherichia coli (ETEC), may also function as a pathobiont, in that there may be unique individual or collective sets of commensal bacteria that protect some humans from disease following challenge [8] and animal models suggest a role for probiotics in the prevention of ETEC diarrhea [9].…”
Section: Colonization Resistance and Infection By Pathobiontsmentioning
confidence: 99%
“…[6] and Camplylobacter spp. [7]. However, early data suggest that even the much more common bacterial cause of traveler’s diarrhea, Enterotoxigenic Escherichia coli (ETEC), may also function as a pathobiont, in that there may be unique individual or collective sets of commensal bacteria that protect some humans from disease following challenge [8] and animal models suggest a role for probiotics in the prevention of ETEC diarrhea [9].…”
Section: Colonization Resistance and Infection By Pathobiontsmentioning
confidence: 99%
“…The mechanisms implicate the release of pathogenic products that may affect both microbiota and host components, modifications of the mucus barrier, redistribution of epithelial Toll-Like Receptors, as well as modulation of host immune responses as least in part by promoting regulatory Tcells that suppress protective responses to inflammatory stimuli [18, 36, 50, 57, 59, 62]. Enteropathogen-modified microbiota directly affect host immunity, and indeed these dysbiotic microbiota are able to cause or exacerbate gut inflammation [18, 19, 36, 45, 59, 62]. Intriguingly, even remote infections, such as respiratory infections with influenza virus, are able to cause gut microbiota dysbiosis [58].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the enteropathogen Campylobacter jejuni is able to modify gut microbiota [61], and to promote the expression of latent virulent genes in non-invasive E. coli , including fimbrial genes ( fimA , sfmF) , flagellar genes ( fliD) , and genes regulating Hemolysin E ( hlyE ); these effects are associated with disruptions of TLR4 gene expression, and promote the release of pro-inflammatory CXCL-8 in human intestinal epithelial cells [19]. Studies also found that exposure to C. jejuni promotes E. coli adherence to, and subsequent translocation through, intestinal epithelial cells [19, 62]. Translocation is facilitated by hijacking the host lipid raft pathway as well as via epithelial M-cells [6264].…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter jejuni also damage the polarity of TLR9, which in turn destroys the TLR9 induced epithelial barrier and increases CXCL8 production indicating that the infection of C. jejuni could induce the inflammatory response of experimental colitis in mice (Reti et al . 2015). Giardia sp.…”
Section: The Mechanism Of Action Of Gut Bacteria In Intestinal Diseasmentioning
confidence: 99%